A Critical Discourse Analysis of Zohran Mamdani’s Mayoral Victory Speech: Textual Dimensions and Political Rhetoric - Aura Savinka Balqis; Muhammad Fakhran al Ramadhan (Universitas Sebelas Maret, 2026)
This research examines the linguistic strategies and ideological meanings embedded in Zohran Mamdani’s 2025 mayoral victory speech by applying Van Djik’s Critical Discourse Analysis framework. Through an exploration of the macrostructure, superstructure, and microstructure, the study shows how Mamdani shapes a progressive political persona, builds a sense of shared agency, and contests the dominance of established power holders. On the macrostructural level, the speech is organized around five key ideas: the reclaiming of political power by working-class groups, the forging of broad-based solidarity, the portrayal of the election win as a historical turning point, the outlining of concrete policy proposals, and New York City’s role in resisting nationwide right-wing movements. The superstructure analysis indicates that the speech combines typical features of victory addresses with rhetorical elements commonly found in social movements, such as collective emotional release and explicit challenges to political opponents. Meanwhile, the microstructural analysis reveals intentional lexical patterns, vivid depictions of labor, extensive use of inclusive pronounse, and recurring metaphors particularly those involving grasping, breathing, and light that help construct its message of transformation.